Dakwah di Era Society 5.0: Integrasi Pendidikan Akhlak Tasawuf untuk Penguatan Kesehatan Mental Mahasiswa - Himawan, Ahmad; Saepullah, Saepullah; Mukarromah, Al (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This research aims to examine the relevance and implementation of Sufism moral education in da'wah in the era of Society 5.0 and its impact on strengthening the mental health of students. The research method uses a qualitative descriptive-analytical approach with literature studies and in-depth interviews with students and lecturers teaching Sufism morals at private Islamic universities. The results show that Sufistic values such as patience, sincerity, trust, and gratitude play a significant role in managing stress and anxiety among students, thereby enhancing mental resilience and emotional well-being. Practices such as dhikr (remembrance of God), self-reflection (muhasabah), and spiritual guidance through mentoring and dhikr communities have been proven effective in strengthening the character and mental health of students amidst high social and academic pressures. The integration of Sufism moral education in the da'wah curriculum in the Society 5.0 era through innovative learning, spiritual communities, and the utilization of digital technology has been shown to contribute significantly to creating holistic and adaptive Islamic education. Sufism moral education becomes a strategic solution in addressing the mental health challenges of students in the digital era by building a balance between technological advancements and human values. This research provides a theoretical and practical foundation for the development of future Islamic education and da'wah oriented towards forming individuals with strong character and mental health.